On certain means of two arguments and their extensions - Edward Neuman; József Sándor (International Journal of Mathematics and Mathematical Sciences)
Inequalities for three means introduced by H.-J. Seiffert are obtained. Generalizations of these means, their basic properties, and inequalities satisfied by the new class of means are also included.